Kualitas Pelayanan di Dinas Tenaga Kerja: Koperasi dan Usaha Kecil Menengah Kota Gorontalo - Muh. Reynaldi F. Mozin; Ismet Sulila; Sri Yulianty Mozin (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2026)
This study aims to analyze the service quality of the issuance of the Job Seeker Card (AK-1) at the Department of Manpower, Cooperatives, and Small and Medium Enterprises of Gorontalo City This study focuses on the five dimensions of service quality based on the SERVQUAL model Tangibles, Reliability, Responsiveness, Assurance, and Empathy The study is conducted based on the decline in the number of job seeker card service users year over year, indicating issues with service quality This study employs a qualitative, descriptive approach Data collection techniques include observation, interview, and documentation Data analysis uses the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The findings show that the service quality at the Department of Manpower. Cooperatives, and Small and Medium Enterprises of Gorontalo City is generally not yet optimal In terms of tangibles, service facilities still need improvement, particularly in the comfort of service rooms In terms of empathy officers have shown concern for the community, but it is not yet consistent across all service situations Responsiveness is considered fairly good, although delays in the service process still occur In terms of reliability, services are not yet fully consistent in providing accurate, precise results Meanwhile, in terms of assurance, officers provide polite and fairly convincing services, although their competence still needs Improvement The conclusion of this study indicates that the service quality of the issuance of the Job Seeker Card at the Department of Manpower Cooperatives, Small and Medium Enterprises of Gorontalo City Still requires improvement, particularly in enhancing facilities, human resource competence and service consistency to increase public satisfaction.